RITUAL NGABEN BIA TANEM DI DESA LEMUKIH PERSPEKTIF PENDIDIKAN AGAMA HINDU - Rahayuni, Komang Sri; Suryawan, IG Agung Jaya; Gunawan, I Ketut Pasek (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the procession, Hindu Religious Education values, and implications of the Ngaben Bia Tanem ritual tradition in Lemukih Village, Sawan District, Buleleng Regency. The research method used is descriptive qualitative, with data collection techniques including non-participant observation, structured interviews with custom leaders, priests (pemangku), and local residents, as well as documentation and literature studies using snowball sampling to select informants. The results show that the Ngaben Bia Tanem procession is uniquely carried out without physical cremation, but through burial and the symbolic use of fruit-bearing plants alongside Tirta Pengentas as a purifier of Agni Niskala to maintain the sanctity of Bukit Cemara Geseng Temple and harmonize the Panca Maha Bhuta. In terms of values, this ritual embodies Tattwa Educational values through understanding the eternal nature of the Atman and the impermanence of the physical body, Susila values that foster mutual cooperation (ngayah), and Upacara values that emphasize the sanctity of the Bali Aga dresta tradition. The implications of this study confirm that the Ngaben Bia Tanem tradition contributes significantly to strengthening Sraddha and Bhakti values, shaping social character, preserving local culture, and reducing the economic burden on village community members (krama desa). Overall, a deep understanding of this ritual serves as an integrated spiritual education medium that reinforces cultural identity and Hindu Religious Education values amidst the dynamics of modernization.